2016
DOI: 10.4238/gmr.15038919
|View full text |Cite
|
Sign up to set email alerts
|

Biplot analysis of strawberry genotypes recommended for the State of Espírito Santo

Abstract: ABSTRACT. Most strawberry genotypes grown commercially in Brazil originate from breeding programs in the United States, and are therefore not adapted to the various soil and climatic conditions found in Brazil. Thus, quantifying the magnitude of genotype x environment (GE) interactions serves as a primary means for increasing average Brazilian strawberry yields, and helps provide specific recommendations for farmers on which genotypes meet high yield and phenotypic stability thresholds. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
2
9
0
6
Order By: Relevance
“…It is important to mention that the estimates of coefficient of variation obtained were lower than 15% for all traits, indicating high experimental precision and credibility of the joint analysis. Estimates of coefficient of variation observed in the joint analysis are similar to those reported in other strawberry studies (RADMANN et al, 2006;MONCADA et al, 2008;RESENDE et al, 2010;RANDIN et al, 2011;COSTA et al, 2015;COSTA et al, 2016). According to Cruz et al (2012), coefficient of variation lower than 20% indicates high experimental precision for quantitative traits, such as those evaluated in this study.…”
Section: Resultssupporting
confidence: 75%
“…It is important to mention that the estimates of coefficient of variation obtained were lower than 15% for all traits, indicating high experimental precision and credibility of the joint analysis. Estimates of coefficient of variation observed in the joint analysis are similar to those reported in other strawberry studies (RADMANN et al, 2006;MONCADA et al, 2008;RESENDE et al, 2010;RANDIN et al, 2011;COSTA et al, 2015;COSTA et al, 2016). According to Cruz et al (2012), coefficient of variation lower than 20% indicates high experimental precision for quantitative traits, such as those evaluated in this study.…”
Section: Resultssupporting
confidence: 75%
“…In the analysis of joint variance there was a significant effect for cultivar, environment and cultivar x environment interactions with regard to NTF, TMF, NCF and MCF (Table 1), demonstrating genetic variability among the cultivars, and inconsistency in their behavior in response to environmental oscillations. Other studies also found interactions between strawberry cultivars and crop environments (Pereira et al 2013;Rosa et al 2013;Costa et al 2015;Costa et al 2016). This shows the importance of studies on stability of strawberry cultivars.…”
Section: Resultsmentioning
confidence: 81%
“…The interaction between phenotype and environment is marked in strawberry crops (Pereira et al 2013;Rosa et al 2013;Costa et al 2015;Costa et al 2016) and restricts the selection and the recommendation of the same cultivar in several environments. Cultivars that adapt to a broader range of environments are common; while others have a limited adaptation to the places they are grown.…”
Section: Introductionmentioning
confidence: 99%
“…Com a existência de genótipos que não se enquadraram em nenhum mega-ambiente (Aliyu et al 2014). Em morango para produtividade já houve um comportamento distinto em que cada local compôs um mega-ambiente (Costa et al 2016), assim como em mandioca (Peprah et al 2016).…”
Section: Resultsunclassified
“…Baseado nestas informações, nenhum genótipo de açaizeiro superou o ideótipo, pois todos os materiais mais produtivos foram também os mais instáveis, similar ao que foi obtido por Aliyu et al (2014) quando avaliou cajueiros para número, peso e produtividade de amêndoas. Quanto à dispersão dos materiais genéticos para pmc e ptc, ocorreu a mesma diversidade que aquela apresentada em morangueiro (Costa et al 2016) e mandioca (Peprah et al 2016), cujas médias dos genótipos não se concentraram próximo da média dos mega-ambientes, enquanto que em ntc a dispersão foi relativamente menor.…”
Section: Resultsunclassified